PENGENALAN PRODUK TENUN SARIGADING DI MEDIA SOSIAL UNTUK MENINGKATKAN PERSEPSI MASYARAKAT - rika novyanti; Tarman Effendi; Novi Shintia (P3M Politeknik Negeri Banjarmasin, 2021)
The media has a very important role in providing a positive or negative influence on consumers in evaluating a product. Along with technological developments, the prestige of social media is widely used as a media repository for communication, especially for millennial children. This study used quantitative methods and consisted of 2 research variables, namely, product knowledge variables and perception variables. The research sampling used purposive sampling technique of 100 people at the voting age of 17 s / d 35 years in Banjarmasin who had participated this year. The results showed that (1) Social media is an application for uploading and sharing photos to other users. In this Sarigading woven product, the introduction method through social media can be done through a business account provided by social media, because it has interesting features so that it can create optimization for a product. (2) the majority of millennials in Banjarmasin use the social media WhatsApp and Instagram (data shows that in Banjarmasin there are 76% for WhatsApp users and 60% for Instagram users), so that the two social media are very appropriate to be used to introduce Sarigading woven products.